The effects of temperature and color value on hydrochars’ properties in hydrothermal carbonization - Li, Hui; Wang, Siyuan; Yuan, Xingzhong; Xi, Yanni; Huang, Zhongliang; Tan, Mengjiao; Li, Changzhu (Bioresource technology, 2018)
[Display omitted] •HTC increased the stability and safety level of the sawdust’s combustion and pyrolysis.•The color of hydrochars turned blacker, greener, and bluer after HTC process.•The ash, carbon, hydrogen and lignin showed a good correlation with color coordinates.•The influence of temperature on hydrochar combustion was investigated by DTG.•The hydrochars pyrolysis was studied by the KAS and Coats-Redfern methods. In order to investigate the influence of hydrothermal carbonization (HTC) on the properties of the hydrochars, sawdust with a particle size below 0.45mm was treated in an autoclave at 200–260°C. The physical and chemical characteristics of products were studied, including proximate analysis, elemental composition, fiber content, surface area, bulk density, energy yield, color value, combustion activities and pyrolysis kinetics, etc. It showed that the color of hydrochars turned blacker, greener, and bluer after HTC. The ash, carbon, hydrogen and lignin contents showed a good correlation (R2>0.96) with color coordinates. The decrement in stage 1 and increment in stage 2 of temperature intervals were attributed to the volatile matters removal and fixed carbon accumulation, improving the stability and safety of hydrochars combustion. As shown by the Kissenger–Akahira–Sunose (KAS) and Coats–Redfern calculations, the HTC process can also make the pyrolysis more stable.